Black phosphorus with near-superhydrophobic properties and long-term stability in aqueous media. Issue 31 (22nd March 2018) - Matthews, Peter D.; Hirunpinyopas, Wisit; Lewis, Edward A.; Brent, Jack R.; McNaughter, Paul D.; Zeng, Niting; Thomas, Andrew G.; O'Brien, Paul; Derby, Brian; Bissett, Mark A.; Haigh, Sarah J.; Dryfe, Robert A. W.; et al.
Abstract : We present the use of a polymeric stabilizer which stymies the degradation of black phosphorus nanosheets in aqueous media as well as imparting superhydrophobic properties to immobilised nanosheets. Abstract : Black phosphorus is a two-dimensional material that has potential applications in energy storage, high frequency electronics and sensing, yet it suffers from instability in oxygenated and/or aqueous systems. Here we present the use of a polymeric stabilizer which prevents the degradation of nearly 68% of the material in aqueous media over the course of ca. 1 month.